Unilateral Nevoid Telangiectasia in a Healthy Man - Kirley Küçük; Florence Bourlond; Nicolas Votquenne; Farida Benhadou (Karger Publishers, 2021)
We report the case of a healthy 26-year-old man presenting telangiectatic macules on the left thorax and arm since childhood. The main diagnostic hypothesis were unilateral nevoid telangiectasia (UNT), hereditary benign telangiectasia, atrial myxoma, segmental serpiginous angioma, circumscribed neviform angiokeratoma, and nevus vascularis mixtus. The diagnosis retained was UNT characterized by congenital or acquired telangiectasia distributed asymmetrically along the upper extremities, or the third or fourth cervical dermatomes. The congenital form is extremely rare, predominant in men, and persists in adulthood. The acquired form is most frequent, affects preferentially women, usually appears at puberty or during pregnancy and tends to disappear. Estrogen excess triggers the formation of telangiectasia. UNT is rarely associated with liver or thyroid disorder. Pulsed-dye lasers and normalization of estrogen are proposed as therapeutic options. We report a rare diagnosis of UNT in a young man with no other underlying condition. We would like to highlight that in the presence of unilateral telangiectasia, a complete clinical examination must be performed to rule out signs of hyperestrogenism in man, ocular or neurological abnormalities, a blood test to exclude pregnancy, hepatic and thyroid dysfunctions, and ultrasonography in case of suspicion of atrial myxoma.